2010
DOI: 10.1002/cphc.201000015
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hybridization in Thermoresponsive Polymer Nanoparticles

Abstract: We achieve very high hybridization efficiencies by using a new method to immobilize DNA strands on the surface of thermoresponsive polymer nanoparticles. Hybridization efficiencies of about 70 % are obtained between the DNA immobilized in the particles and a complementary strand in solution, even at very low ionic strengths (1 mM). The polymer nanoparticles have a glassy poly(methylmethacrylate) (PMMA) core and a thermoresponsive shell of poly(N-isopropylacrylamide) (PNIPAM) containing positive charges. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…52 Importantly, analogous to peptide−PNIPAM systems, DNA and PNIPAM are compatible only in chilled aqueous medium. This was confirmed by recent studies of Moura et al 53 and Martinho et al 54 who were able to immobilize oligonucleotide (OND) and DNA on thermoresponsive shell of PNIPAM, copolymerized with a small amount of positively charged comonomer, aminoethyl methacrylate hydrochloride, in order to increase the absorption of negatively charged DNA and OND. At temperatures lower than PTT, the nucleotides are distributed into the interior of the shell.…”
Section: Biomacromolecules?supporting
confidence: 70%
See 1 more Smart Citation
“…52 Importantly, analogous to peptide−PNIPAM systems, DNA and PNIPAM are compatible only in chilled aqueous medium. This was confirmed by recent studies of Moura et al 53 and Martinho et al 54 who were able to immobilize oligonucleotide (OND) and DNA on thermoresponsive shell of PNIPAM, copolymerized with a small amount of positively charged comonomer, aminoethyl methacrylate hydrochloride, in order to increase the absorption of negatively charged DNA and OND. At temperatures lower than PTT, the nucleotides are distributed into the interior of the shell.…”
Section: Biomacromolecules?supporting
confidence: 70%
“…By increasing the temperature above the phase transition, DNA and OND are anchored in the dense surface layer, not located inside the shell but oriented toward the water phase. Other results, published elsewhere, 53,54 suggest that the incorporation into the TRP of small amounts of hydrophobic, weakly acidic, or basic comonomers is an important factor for successful biomedical and biotechnological applications. In that case, the electrostatic interactions were the dominant force.…”
Section: Biomacromolecules?mentioning
confidence: 95%
“…Stimuli‐responsive colloidal particles have described applications in areas as diverse as the stabilization, destabilization and inversion of colloidal emulsions, foams and suspensions; catalysis; sensors and drug‐delivery [2, 3]. Curiously, few accounts describe the application of stimuli‐responsive nanoparticles in biomolecules separation [4–12], with no reports published, to our knowledge, on mAb purification from mammalian cell cultures. However, thermo‐responsive magnetic particles immobilized with bovine serum albumin (BSA) have been used for the affinity purification of anti‐BSA antibodies from rabbit antiserum [13], while systems envisioned for immunoassays have also used thermo‐responsive particles in antibody‐antigen recognition [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the technique measure the diffusion coefficients of the fluorescent species only, there is no interference of the non-fluorescent free copolymer. Previously characterized dT 25 oligonucleotides labeled at the 5′-terminus with a rhodamine X [27,28,29] showed that the probe has a high quantum yield and good photostability. FCS measurements of the 1:1 and 2:1 SRP:DNA-ROX mixtures yield the diffusion coefficients of the samples, from which the hydrodynamic radius ( R FCS ) can be calculated using the Stokes-Einstein equation.…”
Section: Resultsmentioning
confidence: 99%